2022
DOI: 10.3390/cancers14163989
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome in Spinal Meningioma Surgery and Use of Intraoperative Neurophysiological Monitoring

Abstract: Data on intraoperative neurophysiological monitoring (IOM) during spinal meningioma (SM) surgery are scarce. The aim of this study was to assess the role of IOM and its impact on post-operative functional outcome. Eighty-six consecutive surgically treated SM patients were included. We assessed pre and post-operative Modified McCormick Scale (mMCS), radiological and histopathological data and IOM findings. Degree of cord compression was associated with preoperative mMCS and existence of motor or sensory deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
4
12
0
Order By: Relevance
“…No significant improvements were detected in patients operated with IONM. The authors recommended the use of IONM only in complex cases [ 42 ]. Nonetheless, randomized controlled trials are required to explore the true effect of this methodology on outcomes in spinal meningioma surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant improvements were detected in patients operated with IONM. The authors recommended the use of IONM only in complex cases [ 42 ]. Nonetheless, randomized controlled trials are required to explore the true effect of this methodology on outcomes in spinal meningioma surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Thromboembolic events were the main cause of the few severe complications (Ibanez type 3 or 4, 5.5% of all complications), highlighting the need for preventive measures in the postoperative management of risk patients. There was no evidence to suggest that IONM reduces the frequency of complications [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…All other CSFL occurred in the upper spinal levels above D-6 (N = 5/7, 71.4%). Previous studies also did not demonstrate a higher rate of CSFL in the lumbar spine, 1,2,4,5,18,39,42 questioning the hypothesis that elevated hydrostatic pressure in the lower spinal segment is a risk factor for CSFL.…”
Section: Discussionmentioning
confidence: 94%
“…Intraoperative monitoring was conducted in a standard fashion by recording muscle MEPs and D-wave, as well as eliciting SEPs from all four extremities. 9,10 A commercially available system (Inomed Co, Emmendingen, Germany) equipped with a constant current stimulator was used.…”
Section: Methodsmentioning
confidence: 99%
“…These surgeries differ widely in their neurosurgical and neurophysiologic aspects, and hence, the value of IONM for IMSCT has been obscured. 10 To the best of our knowledge, the question of whether there is any evidence supporting IONM as a preventive tool in intramedullary tumor surgery has been addressed in only two studies, both of which reported level two evidence. Choi et al 35 compared 76 patients who underwent intramedullary tumor surgery without IONM (1998IONM ( -2006 and with IONM (2006IONM ( -2012.…”
Section: The Predictive Value Of Ionmmentioning
confidence: 99%